Diversidade de espécies de Clonostachys no Brasil - Moreira, Gláucia Mara (2016)
The objective of this work was to delineate phylogenetic species from a collection of 106 strains of Clonostachys isolated from different substrates and biomes in Brazil based on multilocus DNA sequence analyses, to determine morphological markers, and describe new species. The fungi were cultivated on MEA and incubated at 10, 15, 20, 25, 30, and 35 ºC during seven days for evaluating growth rate. Pigmentation of the colony was evaluated after seven days on PDA and the micromorphological characters on OA and SNA with fragments of carnation leaves. A DNA fragment of ATP citrate lyase gene (acl1) was sequenced for all strains. Representatives of each identified phylogenetic lineage were selected to obtain DNA sequences of the genes largest subunit of RNA polymerase II (rpb1), translation elongation factor 1-α (tef1), and beta tubulin (tub). Phylogenetic trees were obtained by Bayesian inference (BI) and maximum likelihood (ML) for each gene region and also for concatenated sequences. The phylogeny of concatenated sequences for the four loci using 54 strains of subgenus Bionectria confirmed the identification of C. chloroleuca sp. nov. and the known species C. byssicola, C. rosea, C. rhizophaga, C. pseudochroleuca, and C. rogersoniana, which formed monophyletic groups with high statistical support. The 13 strains of C. pseudochroleuca formed three subclades, being one represented by a morphotype which differs from the other strains. In the preliminary phylogeny of the 52 strains based on acl1 gene two distinct clades were observed within the subgenus Bionectria, with strains morphologically similar to C. compactiuscula, named as C. cf. compactiuscula. Reference sequences of C. compactiuscula were included in the phylogeny of tub gene. The two lineages denominated C. cf. compactiuscula did not group with sequences of this species, representing a putative new species. Representatives of subgenera Zebrinella and Epiphloea were observed. Combined trees of genes acl1-tef1-tub were obtained by BI and ML methods, as well as individual trees for each region gene, confirming the identification of new species Clonostachys sp. 2, inserted in subgenus Epiphloea, together with the known species C. candelabrum. Clonostachys sp. 3 represented a disctinct lineage in the subgenus Zebrinella. The results showed that there is large diversity of Clonostachys in Brazil, with high potential for the discovery of new species or species poorly studied.